2017
DOI: 10.1007/s00018-017-2590-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of long-distance transport of mitochondria along microtubules

Abstract: Mitochondria are cellular organelles of crucial importance, playing roles in cellular life and death. In certain cell types, such as neurons, mitochondria must travel long distances so as to meet metabolic demands of the cell. Mitochondrial movement is essentially microtubule (MT) based and is executed by two main motor proteins, Dynein and Kinesin. The organization of the cellular MT network and the identity of motors dictate mitochondrial transport. Tight coupling between MTs, motors, and the mitochondria is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 120 publications
0
64
0
Order By: Relevance
“…Among these, dynein is mostly responsible for the intracellular transportation of the flagella [36]. Microtubule-based cytoskeleton functions in concert with dynein to support the transport of cargoes across the mammalian cell cytosol, including the mitochondria, chromosomes, and other cell organelles [37,38]. Dynein 1 was highly expressed in the TES of this study, and it serves as the engine to support the transport of spermatids and organelles across the seminiferous epithelium during spermatogenesis [39].…”
Section: Genes Encoding Microtubule-based Motor Proteinsmentioning
confidence: 68%
“…Among these, dynein is mostly responsible for the intracellular transportation of the flagella [36]. Microtubule-based cytoskeleton functions in concert with dynein to support the transport of cargoes across the mammalian cell cytosol, including the mitochondria, chromosomes, and other cell organelles [37,38]. Dynein 1 was highly expressed in the TES of this study, and it serves as the engine to support the transport of spermatids and organelles across the seminiferous epithelium during spermatogenesis [39].…”
Section: Genes Encoding Microtubule-based Motor Proteinsmentioning
confidence: 68%
“…Studies have shown that MT-based cytoskeleton that appears as tracklike structures is working in concert with MT-specific motor proteins (e.g., dynein 1) to support the transport of cargoes across mammalian cell cytosol, including mitochondria, chromosomes, and numerous cell organelles (4,5,8,12,59). Thus, when the heavy chain of cytoplasmic dynein 1, a minus-end-directed MT motor complex, namely Dync1h1, was silenced in the testis in vivo, it impeded the transport of developing spermatids and other cellular organelles, such as residual bodies and phagosomes, across the seminiferous epithelium during the epithelial cycle to support spermatogenesis and cell polarity.…”
Section: Discussionmentioning
confidence: 99%
“…6M ). Interestingly, while microtubules and their motors have been established as important factors for mitochondrial transport 40 , emerging evidence indicates that mitochondria interact with the actin cytoskeleton in many cell types 41-43 . Although we could track single mitochondria and measure their velocity by live imaging, the motors involved in their transport through iTNTs, as well as the motors involved in the transport of the different vesicular structures, remain to be identified.…”
Section: Discussionmentioning
confidence: 99%